Calcium phosphate scaffolds with defined interconnecting channel structure provide a mimetic 3D niche for bone marrow metastasized tumor cell growth. (1st April 2019) - Aveic, Sanja; Davtalab, Roswitha; Vogt, Michael; Weber, Michael; Buttler, Patricia; Tonini, Gian Paolo; Fischer, Horst
Graphical abstract: Abstract: Metastasis of tumor cells in the bone marrow (BM) is a multi-step and highly dynamic process during which cells succumb important phenotypic changes. Behavior of disseminated tumor cells in BM is strictly regulated by three-dimensional (3D) cell-cell and cell-matrix interactions. In this study, we explored whether the β-tricalcium-phosphate (β-TCP) scaffolds with a tailored interconnecting channel structure could enable appropriate 3D mimetic BM microenvironment for the growth of metastatic neuroblastoma cells. The scaffolds provided the mechanical support for human mesenchymal stromal cells (hMSC) allowing them to proliferate, differentiate towards osteoblasts, and produce the deposits of extracellular matrix inside the interconnected channels. The in vitro microenvironment shaped by stromal cells was then tailored by neuroblastoma tumor cells. Immunohistological analyses confirmed the organization of tumor cells into the forms of spheres only when co-cultured with hMSC-derived osteoblasts. The growing rate of tumor cells in 3D conditions was less marked comparing to the one of the cells grown as 2D monolayer as confirmed by decreased Ki-67 expression. Instead, the 3D culturing of neuroblastoma cells inside supportive stroma promoted cell quiescence as sustained by increased p27 level. A balance between cell proliferation, survival, and differentiation was more evident for tumor cells grown inside the 3D scaffolds, thus mirroring better the situation that occurs in vivo where the cells do not follow the exponential growth rate. We conclude that the proposed 3D β-TCP scaffold type provides a mimetic 3D in vitro niche suitable for studying behavior of BM metastasized tumor cells. Statement of Significance: Bone marrow (BM) niche is a favorite target of metastatic neuroblastoma cells. To better address the molecular mechanisms that sustain spatiotemporal organization of neuroblastoma cells in the marrow we mimicked the three-dimensional (3D) assembly of stromal and tumor cells inside β-tricalcium-phosphate (β-TCP) scaffolds. β-TCP scaffolds with a tailored interconnecting channel structure provided mechanical support to mesenchymal stromal cells allowing them to differentiate towards osteoblasts and to produce extracellular matrix. A dynamic cell-matrix interplay favored the characteristic rosette-like growth of metastatic neuroblastoma cells and triggered their quiescence. With our study, we confirmed the potential of β-TCP scaffolds with reproduced BM niche as a cost-effective in vitro model for the growth of disseminated tumor cells, and for related biological and pharmacological surveys.